Income Contribution of Backyard Gardening and its Association with Household Food Security: A Case Study in an Urban Setting - Aphane, Thabang R.; Muchopa, Chiedza L. (International Journal of Economics and Financial Issues, 2024)
Households located in urban township settings experience food insecurity which can be alleviated through backyard gardening. This study is to determine the extent of the contribution of backyard gardening to food security. Based on the Logistic Regression Model, household size, farming experience, employment status of the household head and harvesting frequency were found to be significant in affecting the food security status of the household. The study found that backyard gardening contributes (contribution index of 67.25%) towards household food security. Household specific factors should therefore be considered in policy targeted intervention strategies aimed at alleviating food insecurity.